First experience of implanting AMS 800 urinary sphyncter - Černiauskienė, Aušra; Valatka, Paulius (Lietuvos chirurgija, 2017)
Objective Our purpose is to provide first results of artificial urinary sphincter AMS 800 implantation for treatment of male urinary incontinence after radical prostatectomy. To evaluate effectiveness and safety of AMS 800 artificial urinary sphincter patients. Material and methods 2016-11-04 three patients with severe urinary incontinence after radical prostatectomy had artificial urinary sphincter AMS 800 implantation. For these patients, urinary incontinence conservative treatment has not effective. All patients before surgery examined. For all patients progression of prostate cancer, urethral strictures, residual urine and urinary tract infections were not found. Patients were checked one month after the activation of the artificial sphincter. Results Three artificial sphincters were implanted in 3 patients. After six weeks has been activated 2 sphincters, one sphincter was not activated because of device failure, however, one week later artificial sphincter was reactivated successfully. After checking the 3 patients within 1 month after the activation of the sphincter, for 2 patients wasn’t need sanitary pad and for one patient was enough just 2 pads.
Keywords: male urinary incontinence; artificial urinary sphincter; radical prostatectomy; AMS 800